SLC7A11-mediated cell death mechanism in cancer: a comparative study of disulfidptosis and ferroptosis - Wen-Wen Zhu; Ying Liu; Ze Yu; Hong-Qiang Wang (Frontiers in Cell and Developmental Biology)
SLC7A11: also known as Sodium-Coupled Neutral Amino Acid Transporter 11, is an essential transporter protein that plays a vital role in the intracellular transport of amino acids, especially cysteine. Recently, its involvement in cell death mechanisms has attracted considerable interest, underscoring its significance in both normal physiological functions and various disease states. This paper aims to provide a thorough overview of current understanding of the role of SLC7A11 in two specific types of cell death: disulfidptosis and ferroptosis. We highlight the dual functions of SLC7A11 in these processes, examining how its activity changes under different pathological conditions and what this means for potential therapeutic approaches. In this study, we clarify the regulatory mechanisms governing SLC7A11 and its influence on cell death, ultimately presenting new insights that could guide future research in targeted therapies.